2005
DOI: 10.1111/j.1365-2265.2005.02367.x
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between BRAFV600E mutation and clinicopathological features of papillary thyroid carcinomas in Taiwan

Abstract: BRAFV600E mutation is the most prevalent oncogene in PTCs in Taiwan. Our data did not suggest that BRAFV600E mutation could be a potentially useful marker of prognosis in patients with papillary carcinomas in the population studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 32 publications
10
87
2
3
Order By: Relevance
“…The most prevalent subgroup of classical and follicular variants of PTC showed no association of BRAF mutation with poor prognostic factors or poor outcome. Our findings corroborated recent studies (20,21,22,23) and also discarded the association of p.V600E with higher frequency of cervical LN and distant metastases (13,24,25,26). In order to justify the lack of association, it has also been proposed that it is not the intratumoral presence of BRAF mutation that determines prognosis but the higher frequency of mutant BRAF alleles, identified in an innovatory analysis of pyrosequencing technique, that favors more frequent recurrence (27).…”
Section: Clinical Study D L S Danilovic and Others Preoperative Molecsupporting
confidence: 80%
“…The most prevalent subgroup of classical and follicular variants of PTC showed no association of BRAF mutation with poor prognostic factors or poor outcome. Our findings corroborated recent studies (20,21,22,23) and also discarded the association of p.V600E with higher frequency of cervical LN and distant metastases (13,24,25,26). In order to justify the lack of association, it has also been proposed that it is not the intratumoral presence of BRAF mutation that determines prognosis but the higher frequency of mutant BRAF alleles, identified in an innovatory analysis of pyrosequencing technique, that favors more frequent recurrence (27).…”
Section: Clinical Study D L S Danilovic and Others Preoperative Molecsupporting
confidence: 80%
“…These results are in agreement with those reported in other series (Kim et al 2005, Liu et al 2005, Trovisco et al 2005. On the contrary, previous data on the association of B-RAF with a worse stage and/or local or distant metastases or recurrence (Namba et al 2003, Xing 2005 are not confirmed in the present large series.…”
Section: Discussioncontrasting
confidence: 52%
“…At present, no other unequivocal correlations between genotype and clinico-pathologic features of PTC patients have been reported both in previous reports from the present authors (Fugazzola et al 2004, Puxeddu et al 2004) and in other more recent studies (Sedliarou et al 2004, Kim et al 2005, Liu et al 2005, Trovisco et al 2005. A few studies (Namba et al 2003, Xing 2005 have shown a correlation of B-RAF V600E with more advanced stage, nodal/distant metastases at diagnosis or tumor recurrence.…”
Section: V600ementioning
confidence: 66%
“…At variance with RET/ PTC, BRAF (V600E) positive PTCs were not found to be in relationship to previous radiation exposure (Nikiforova et al 2004); no other environmental factors has been identified that favors BRAF (V600E) mutation. Several studies tried to establish a correlation between BRAF (V600E) and the clinical features of PTCs, but results have been controversial (Lee et al 2007, Xing 2007: in some studies, BRAF (V600E) was associated with a more advanced tumor or a more aggressive phenotype (Namba et al 2003, Nikiforova et al 2003, Kim et al 2004, 2006a,b, Oler et al 2005, Powell et al 2005, Jin et al 2006, Riesco-Eizaguirre et al 2006, Kebebew et al 2007, Rodolico et al 2007, while other studies did not find this association (Fugazzola et al 2004, Puxeddu et al 2004, Kim et al 2005, Liu et al 2005, Trovisco et al 2005, Jo et al 2006, Park et al 2006, Sapio et al 2006, Abrosimov et al 2007, Durante et al 2007, Mitsiades et al 2007; see Table 1). Kim et al (2006a) 203 Korea Kim et al (2006b) 103 USA (CA) 100 Korea Riesco-Eizaguirre et al…”
Section: Introductionmentioning
confidence: 99%